2019
DOI: 10.17531/ein.2019.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Competence allocation planning robust to unexpected staff absenteeism

Abstract: Article citation info: (*) Tekst artykułu w polskiej wersji językowej dostępny w elektronicznym wydaniu kwartalnika na stronie www.ein.org.pl Eryk SzwArc Grzegorz BocEwicz zbigniew BAnASzAk Jarosław wikArEkCompetenCe alloCation planning robust to unexpeCted staff absenteeism planowanie przydziału kompetenCji odpornego na nieprzewidziane absenCje praCowników*In order to deal with unexpected events such as employee absenteeism and/or a demand for personnel that is higher or lower than expected, organizations nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Previous research (Szwarc, et al, 2019a(Szwarc, et al, , 2019b shows that because of the computational complexity of the discussed problem (f(n,m) = O(2 m•n ), where: m -number of employees, n -number of activities), in special cases, all variants of competence frameworks (in the example under consideration it is 2 88 variants) have to be checked to obtain a solution.…”
Section: Proactive Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research (Szwarc, et al, 2019a(Szwarc, et al, , 2019b shows that because of the computational complexity of the discussed problem (f(n,m) = O(2 m•n ), where: m -number of employees, n -number of activities), in special cases, all variants of competence frameworks (in the example under consideration it is 2 88 variants) have to be checked to obtain a solution.…”
Section: Proactive Approachmentioning
confidence: 99%
“…In previous studies (Szwarc, et al, 2019a(Szwarc, et al, , 2019bBocewicz, et al, 2020), we developed a model of the synthesis of disruption-robust competence frameworks. That model was limited to situations in which there was just one type of disruption: employee absenteeism (an absence of one, two, or three employees).…”
Section: Proactive Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The maintenance process in enterprises was not always carried out in a way that ensures the minimization of outlays while maximizing the achieved effects in service and maintenance processes. In practice, obtaining the maximum benefits from the operation of a technological machine system requires an optimal solution to a number of tasks [12,13]. For a larger number of machines, it creates the need for appropriate system modelling, simulation research, and optimization of partial and complex tasks based on the adopted optimization criteria [14].…”
Section: Introductionmentioning
confidence: 99%
“…The study reported in this paper is a continuation of our previous work that explored methods of rapid prototyping of workforce-allocation solutions and personnel scheduling problems robust to the disruptions occurring in the course of the execution of multiple projects [11][12][13]. The main contributions of this paper are given below:…”
Section: Introductionmentioning
confidence: 99%